The effect of synthesis temperature on structural, morphological, and band gap energy of plate-like Bi4Ti2.95V0.05O12 prepared by molten NaCl/KCl salt method - Maryani, Kanty; Anwari, Nelly Safitri; Safitri, Widiya Nur; Hardian, Arie; Inggarwati , Ervina Dwi; Prasetyo, Anton (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Vanadium (V)-doped Bi4Ti3O12 compound is reported to have good photocatalyst properties; however, efforts still need to improve the ability of the photocatalyst through various strategies, such as controlling the morphology and particle size. The molten salt method is one of the simple synthesis methods reported successful in synthesizing Bi4Ti3O12 compounds with plate-like/sheet morphology and reported having good photocatalyst activity. One of factor influenced to particle compound obtained by molten salt method is synthesis temperature. Therefore, in this work, V-doped Bi4Ti3O12 (Bi4Ti2.95V0.05O12) was prepared through the molten salt NaCl/KCl method at various synthesis temperatures: 700, 750, and 800?C and the effect of temperature synthesized on (a) structural (b) morphological, and (c) band gap energy were studied. These studies used X-ray diffraction data (diffractogram), scanning electron microscope (SEM) and diffuse reflectance ultraviolet-visible spectroscopy. The diffractograms showed that the target compound was successfully obtained at all temperature synthesis. The crystallographic data indicated that temperature synthesis determined the lattice parameter values. However, there are no clear trend changes that is possibly due to changes in the valence of the V atom. The synthesis temperature also causes increasing the crystallite size but does not affect the crystallinity samples. SEM images showed that all samples had plate-like/sheets morphology and the particle size became larger at higher temperature. It indicated that the particle growth rate was faster than nucleation rate. Meanwhile, the result of Kubelka-Munk calculation showed that all samples had relatively same band gap energy value (Eg(1) was 2.90, and Eg(2) was 1.85 eV.